Proper Name Belarus and its Variants in the Ukrainian Poetic Discourse: Pragmatic and Stylistic Potential (Linguostylistic Studies, 2019)
Few attempts have been made to study the problem of the pragmatic and stylistic potential of the toponym Belarus in the Ukrainian poetry. Among those few there are brief general studies of the expressive and stylistic features of Belarusianisms in Ukrainian (V. Chabanenko) or phonosemantics of onyms in the poetry of the poets of the 60s (Sixtiers) (T. Mozharova). The purpose of the article is to study the realization of the expressive potential of the proper names derived from the lexeme Belarus in the Ukrainian poetry.Ukrainian folklore and literary poetic texts were involved in the analysis. The study uses a descriptive method which is traditional for linguistics and which enables a detailed explanation of the pragmatic and stylistic features of the names of Belarus in poetry; a method of contextual analysis that enables the analysis of toponyms in various communicative situations and interactions with other words in specific poetic texts and a comparative method for comparing the similarities and differences in the use of toponyms in the fiction texts of different authors.The results of the research manifest that the proper names Belarus (Bilorus, Bilorusia, Bila Rus, BSSR, etc.) demonstrate positive-evaluative connotations, peripheral nature of geographical semantics in Ukrainian poetry, actualizing a wide range of implicit values and conveying cultural information about Belarusians. The study has not revealed any single case when the toponym Belarus or its variants become a representative of the “alien” dimension for the lyrical hero in the corresponding binary opposition or has pejorative shade of meaning in the analyzed discourse. Artistic interpretation of the name Belarus and its variants often manifests itself as anthropomorphic metaphorization. The main ways of creating this stylistic device are: the actualization of the semantics of consanguinity, direct author’s characteristics (epithets), use of the verbs that identify Belarus as a person performing an action or the object of interpersonal relations, sacralization of the toponym. Key words: onym, toponym, burial, choronym, expressiveness, cultural information of the name. SourcesDrach, Ivan. Berlo: Knyha poezii. Kyiv : Hramota, 2007.Ellan-Blakytnyi, Vasyl. Poezii. Kyiv : Radianskyi pysmennyk, 1964.Yovenko, Svitlana. Bezsmertia lastivky. Kyiv : Dnipro, 1989. Izdryk, Yurii. Pislia prozy: poeziia. Chernivtsi : Meridian Czernowitz; Knyhy- ХХІ, 2013.Irvanets, Oleksandr. Satyrykon-XXI. Kharkiv : Folio, 2011.Kononenko, Danylo. «Ukrainskoiu — «dzhereltse», biloruskoiu — «krynichka»!» Krymska svitlytsia, № 24, 2004.Kryzhanivskyi, Stepan. Litopys: vybrane. Kyiv : Dnipro, 1991.Lubkivskyi, Roman. Ramena: poezii. Kyiv : Dnipro, 1969.Lutsenko, Dmytro. Use liuboviu zmiriane do dna: liryka, poemy, pisni. Kyiv : Ukrainskyi pysmennyk, 1994.Malyshko, Andrii. Poetychni tvory. Literaturno-krytychni statti. Kyiv : Naukova dumka, 1988.Malyshko, Andrii. Tvory. 10 vols. Kyiv : Dnipro, 1974.Masenko, Teren. Bahriani zhorzhyny. Kyiv : Dnipro, 1969.Masenko, Teren. Vybrane. Kyiv : Dnipro, 1975.Nekhoda, Ivan. Poezii. Kyiv : Radianskyi pysmennyk, 1982.Oles, Oleksandr. Tvory. 2 vols. Kyiv : Dnipro, 1990.Oliinyk, Borys. Vybrane : poezii, poemy. Kyiv : Etnos, 2009.Pavlychko, Dmytro. Virshi z Maidanu. Kyiv : Osnovy, 2014.Pavlychko, Dmytro. Nostalhiia. Poezii. Kyiv : Osnovy, 1998.Pavlychko, Dmytro. Tvory. 3 vols. Kyiv : Dnipro, 1989.Rylskyi, Maksym. Zibrannia tvoriv. 20 vols. Kyiv : Naukova dumka, 1983-1990.Rudanskyi, Stepan. Usi tvory v odnomu tomi. Kyiv, Irpin : Perun, 2007.Synhaivskyi, Mykola. Dorohoiu zori. Kyiv : Molod, 1979. Synhaivskyi, Mykola. Zapovitnyi khlib. Kyiv : Radianskyi pysmennyk, 1982.Synhaivskyi, Mykola. Rodove derevo. Kyiv : Radianskyi pysmennyk, 1988.Sosiura, Volodymyr. Vybrani tvory. 2 vols. Kyiv : Naukova dumka, 2000.Sosiura, Volodymyr. Tvory. 10 vols. Kyiv : Dnipro, 1970-1971.Sosiura, Volodymyr. «Bilorus». Chervonyi shliakh, no 7, 1928, p. 5.Ukrainska literatura XVIII st. Poetychni tvory, dramatychni tvory, prozovi tvory. Kyiv : Naukova dumka, 1983.Ukrainska poeziia. Seredyna ХVІІ st. Kyiv : Naukova dumka, 1992. ReferencesBrailko, Yulia. “Functionality of the Toponym Moscow in the Ukrainian Poetic Discourse”. Mova: klasychne – moderne – postmoderne, iss. 4, 2018, pp. 5–19.Dantsevich, Elena. “Assotsiativnoe pole kontsepta «Belarus'» u uchashchikhsya rannego yunosheskogo vozrasta”. Vestsі BDPU. Seryya 1 : Pedagogіka. Psіkhalogіya. Fіlalogіya, no 3, 2002, pp. 35–8.Іl'chenko, І. І., and Іsachuk, N. V. “Toponіmi v perekladnikh poezіyakh V. A. Chabanenka”. Fіlologіchnі nauki v umovakh suchasnikh transformatsіynikh protsesіv: materіali mіzhnarodnoї naukovo-praktichnoї konferentsії, 10-11 listopada 2017 roku, m. L'vіv. L'vіv : LOGOS, 2017, pp. 31–5.Krasavina, Valentyna. “Vid maidanu do Maidanu”. Kultura slova, iss. 82, 2015, pp. 102–8.Mozharova, Tamara. “Fonosemantyka onimnykh naimenuvan u poezii shistdesiatnykiv”. Lіngvіstichnі doslіdzhennja, iss. 27, 2009, pp. 39–47.Slesareva, T. P. “Onimy Yana Barshchevskogo (na materiale «Shlyakhticha Zaval'ni»): semanticheskiy aspekt”. Nauka – obrazovaniyu, proizvodstvu, ekonomike : materialy XVI(63) Regional'noy nauchno-prakticheskoy konferentsii prepodavateley, nauchnykh sotrudnikov i aspirantov, 16-17 marta 2011, g. Vitebsk. Vol. 1. Vitebsk, 2011, pp. 271–3.Stepanenko, Mykola. “Ukrainska mova i suspilno-politychni transformatsii sohodennia”. Ukrainska mova, no 2, 2015, pp. 3–23.Chabanenko, Viktor. “Ekspresyvno-stylistychni funktsii bilorusyzmiv v ukrainskii movi”. Kultura slova, iss. 17, 1979, pp. 15–26.Yas, O. V. “Bila Rus (Bilorusiia, Bilorus, Bilarus)”. Entsyklopediia istorii Ukrainy, edited by V. A. Smolii. Vol. 1. Kyiv : Naukova dumka, 2003.